Maltreatment history and internalizing and externalizing symptoms in out-of-home care: A three-level meta-analysis - Magalhães, E. (2023)
Background/Aim: Young people in care may show significant mental health difficulties because of previous adverse experiences, such as maltreatment or violence. However, no meta-analyses have been conducted on this topic. We aim to identify the role of previous maltreatment in current symptoms of children and adolescents in out-of-home care. Method: A search in Academic Search Complete, PsycArticles, PsycInfo, Psychology and Behavioral Sciences Collection, ERIC, Medline, Web of Science and Scopus databases was conducted. Studies were included if they were empirical and quantitative, involved school-aged children and adolescents, assessed maltreatment before placement in care and current internalizing and externalizing symptoms. Multiple effect sizes were extracted from each primary study, and a three-level meta-analysis for each type of maltreatment associated with internalizing and externalizing symptoms was conducted. Results: The search yielded 122 effects sizes from 28 studies. Results indicated significant overall effects of general maltreatment (r =.260), abuse (emotional/physical) (r =.135) and sexual abuse (r =.247) on internalizing symptoms. In relation to externalizing symptoms, overall effects of abuse (emotional/physical) (r =.097) and sexual abuse (r =.187) were identified. The overall effect sizes of neglect were neither significant for internalizing or externalizing symptoms. A set of moderators was tested, and significant effects were found for the type of maltreatment measure on internalizing symptoms and for gender on externalizing symptoms. Conclusions: This study provides new insights beyond previous systematic reviews, as we were able to disentangle the associations between maltreatment and internalizing and externalizing symptoms in out-of-home care.